1986
DOI: 10.1177/004057368604300206
|View full text |Cite
|
Sign up to set email alerts
|

The Afrikaner and South Africa

Abstract: “The religious roots of Afrikaner nationalism … can be traced back … to the influences of Reformed evangelicalism, Kuyperian Calvinism, and Romantic nationalism… As of last year, however, the entire scene has changed fundamentally and permanently… What we see unfolding has the makings of a classical Greek tragedy.”

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It was also found that the propane conversion and the propene selectivity is often inversely related. , Generally, the activity and selectivity of the catalyst depends on its reducibility and basicity . To achieve high activity and selectivity the presence of highly dispersed vanadium is crucial. , It is found that at low loadings vanadium is molecularly dispersed, whereas at higher loadings V 2 O 5 crystallites start to appear. …”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the propane conversion and the propene selectivity is often inversely related. , Generally, the activity and selectivity of the catalyst depends on its reducibility and basicity . To achieve high activity and selectivity the presence of highly dispersed vanadium is crucial. , It is found that at low loadings vanadium is molecularly dispersed, whereas at higher loadings V 2 O 5 crystallites start to appear. …”
Section: Introductionmentioning
confidence: 99%
“…As a new use of ammonia, on-site NO x reduction by ammonia, 1,2 especially on ships and stationary facilities, is increasingly important because the worldwide regulations for NO x emission are becoming severe. 3 The achievement of an on-site system should require a small-scale and efficient ammonia synthesis process that can be conducted at all sites of NO x emission. However, at present, ammonia is synthesized on a large scale by the Haber-Bosch process at high temperature ͑ϳ750 K͒ and high pressure ͑ϳ10 MPa͒, 4 and it is still difficult to synthesize ammonia efficiently on a small scale at lower temperature and pressure.…”
mentioning
confidence: 99%
“…According to them it implied political isolation-for-survival (Bosch 1986). In this regard Dubow (1991:11) (Kuyper 1931:35-36;also in Bosch 1986:209-210).…”
Section: [T]he Developing Crisis In Agriculture the Proletarianisatimentioning
confidence: 99%